Analysis of nutritional status in children with intellectual disability during covid-19 pandemic - Erick Burhaein; Irfatoni Irfatoni; Romy Abdul Rozak; Lili Kusmiati; Agus Setiabudi; Carla Cristina Vieira LourenÇo; Miftah Muhammad Basit (JPK (Jurnal Pendidikan Khusus), 2022)
The aim of the study was to look at students' physical fitness conditions based on nutritional status (BMI) during the COVID-19 pandemic. The participants of this study were 28 intellectual disability (ID) students. This research instrument is a test of height and weight that has been standardized. Data analysis uses quantitative descriptive statistics. The results showed that measurements in boys are known as obesity is 1 boy (7,14%), overweight is 6 boys (42,86%), normal is 5 boys (35,71%), thinness is 2 boys (14,27%), and very thinness is 0 (0%). . The results showed that measurements in boys are known obesity is 3 girls (21.43), overweight is 4 girls (28,57%), normal is 3 girl (21.42%), thinness is 3 girl (21.42%), and very thinness is 1 girl (7.14%). The results of the study and discussion above concluded that the nutritional status of children aged 13-15 years during the COVID-19 pandemic was physically examined based on the status of the majority of BMI majority in obesity groups for boys and girls. Contribution for future studies, especially need to include several independent variables to determine the dominant variable that protects the nutritional status of children.